(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Business owners are entities or organizations that engage in professional activity. They may be industrial, commercial, or other types. Setting and obtaining difficult goals in business, responding quickly when necessary, dominating the competition, and motivating others to attain their best potential. Ineffective management can harm the company and cause it to go bankrupt. Toxic workplace attitudes, staff segregation, the departure of high-performing workers, and an unappealing workplace culture will all occur. The sole proprietorship and partnership groups of respondents’ assets showed that Democratic had a 4.86 weighted mean and Coaching leadership styles got 4.56. Both had the greatest overall impact on a business system, which is equal to Very Strongly Agree. The respondents indicated that there are significant differences between the two sets of respondents’ evaluations of the cited variables. One of the challenges faced by the two groups of respondents is a lack of management skills. The main objective of this research was to identify the leadership style and improvements required to support the growth and success of the company. There are four Leadership Styles that are in this study which are: Autocratic, Democratic, Coaching, and Laissez-faire. There is never any doubt about who has the last say when an autocratic leader is in charge, whether it’s about a crucial business choice or how the organization is governed. Since one person is in charge in this leadership style setting, things typically go smoothly and efficiently when roles, rules, and procedures are clearly defined. Democratic leadership, a style of participant leadership, is a leadership style in which group members take a more participative role in the decision-making process. Employees meet to discuss and resolve issues by giving everyone some opportunity to contribute to decisions. Recognizing team members’ abilities, motivations, and areas for improvement is a key component of coaching leadership. Meanwhile, laissez-faire leaders should give their followers the freedom to run their own desks and make their own judgments. When necessary, they provide their staff with help, direction, counsel, and training, but they rely on them to manage the specifics and carry out their jobs and projects.